PERANCANGAN TES ONLINE BERBASIS WEB MENGGUNAKAN METODE FISHER-YATES SHUFFLE (Information Technology and Telematics, 2015)
Abstract Test is one way used by teacher to know students ability. The school majority usually uses manual test to know their students ability. The weakness of using manual test is that it will lessen the effectiveness of the students. In this case, the students still have to prepare stationery, etc. Moreover, there are often cheating cases between students or students are doing cheating during the test. The purpose of this research is to design online test application which has function to show test questions randomly by using Fisher-Yates Shuffle. The development method that used in this school report online test design is using prototype method, whereas the system design is using UML (Unified Modeling Language). The software that is used in this online application design areMySQL, PHP and XAMPP as the local server. This research results an online test application that is able to show the test questions randomly, so it will minimize the cases of cheating while a test is conducted. Moreover, it will facilitate the teachers to give a score marking, because the score will appear automatically from the system. Key words :Online test,studentsphp, mysql.